The study of oxidative stress response in Xanthomonas spp. - Paiboon Vattanaviboon (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Xanthomonas is one of the important genus of phytopathogenic bacteria. In order to successfully colonize the host plant, pathogens must overcome oxidative stress generated as the initial plant defense response. The response to exogenous oxidative stress in Xanthomonas was investigated. Exposure of X. oryzae pv. oryzae (Xoo) as well as X. campestris pv. phaseoli (Xp) to sublethal doses of H2O2 confers protection to H2O2 killing (adaptive response). No adaptive response to tert-butylhydroperoxide (tBOOH) or superoxide generator menadione (MD) was observed. However, exposure to low doses of tBOOH induced cross-protection against H2O2 killing. Pre-treatment with MD conferred cross-protection against H2O2 and tBOOH killing. The levels of protection against H2O2 killing were correlated with their ability to induce catalase. Both adaptive and cross-protective responses require de novo protein synthesis. Pretreatment of Xp with low inducing concentrations of thiol reagents such as N-Ethylmaleimide (NEM) and diamide induced resistance to H2O2 killing. Thiol reagent-induced responses required a functional redox sensor/transcription activator oxyR and were absent in an oxyR mutant. By contrast, NEM pretreatment enhanced the killing effects of organic peroxide. Hydroxyl radical was a major reactive oxygen species involved in H2O2 killing of Xp. Compounds capable of absorbing hydroxyl radicals (glycerol and DMSO) protected Xp from H2O2 killing but not from killing by MD and tBOOH. Addition of ferrous ions to Xp suspension in water potentiated H2O2 killing. On the other hand, pre-treatment of Xp with an iron chelator showed no protective effects and H2O2 killing was actually enhanced. Xp possessed at least two distinct isozymes of monofuctional catalases, denoted Kat1 and Kat2. Kat1 was expressed throughout the growth phase and could be induced in response to exposure to oxidative stresses in the manner of functional oxyR dependence. Kat2 expression was specific to stationary phase of growth. The Xanthomonas-specific kat fragment was amplified from Xp genomic DNA. This specific kat probe was used as a DNA probe to screen a functional kat gene from Xp genomic library constructed in a ZipLox phage vector by plaque hybridization. By this method, a katE gene encoding Kat2 was cloned and characterized. KatE deduced amino acid sequence shows high degree of identity to group II bacteria monofunctional catalase. The role of katE against external peroxide and superoxide killing was evaluated in a mutant strain lacking functional katE. No significant differences were observed in either log or stationary phase cells. The level of total catalase activity in the katE mutant was similar to that of wild type even in stationary phase cells. This result implies the existence of a compensatory mechanism between two catalase isozymes.